Zweistufige Trajektorienplanung für das automatische Einparken - Müller, Bernhard; Deutscher, Joachim (AUTOREG 2006, 2006)
In this contribution a two-step algorithm generating a trajectory for an autonomous parking maneuver is presented. First, a collision-free curve between a given start and a desired goal position within the parking space is planned ignoring the kinematic restrictions on the movement of the car. Second, the collision-free curve is converted into a feasible collision-free trajectory, which can be exactly followed by the ca